KAJIAN KONTRIBUSI SISTEM AGROFORESTRI TERHADAP PENDAPATAN PETANI (Studi kasus : Desa Cibatok Dua, Kecamatan Cibungbulang, Kabupaten Bogor, Provinsi Jawa Barat) - Mardyantoro, Asep; Muttaqien, Zaenal; Lidiawati, Ina (Universitas Nusa Bangsa, 2015)
The development of private forests can provide benefits for farmers because timber commodity has a good selling point. In addition, there is added value if the farmer combining forestry commodity with other commodities such as fruits and crops. Farmers in the Cibatok Dua Village develop private forests and earn additional income for their household needs. This study aims to calculate the contribution of agroforestry in the management of private forests in Cibatok Dua Village to farmers income and identify the types of forestry plants, fruit trees, and the types of agricultural crops with agroforestry systems in the Cibatok Dua Village. The results showed that farmers develop simple agroforestry system with intercropping patterns. That system combining forest trees and agricultural crops as well as fruits between them. The tree that planted was Albisia (Albizia moluccana) and intercropped plants were banana, papaya, coconut, sweet potato, cassava, maize, yam, cloves, pandan, and galangal. Yields from community forests contributes 36% of the total income of farmers. Based on the financial analysis performed by the Discounted Cash Flow method, obtained NPV of Rp 64,197,125, IRR 15%, and Net B / C 2. It means that private forest management by Cibatok Dua Village farmers is financially feasible.